EFFECTS OF P SIOLOGICAL DOSES OF VIT 4 IN D3 (CHOLECALCIFEROL) ON UCED MOLTING GROWTH IN G T FRES ATER P MACROBRACHIUM ROSENBERGII (de Man) - Metar, S. Y.; Srivastava, P. P.; Jain, K. K.; Manush, S. M.; Raizada, S.; Ayyappan, S. (Journal of Indian Fisheries Association, 2015)
Effects of three different doses of vitamin D3 on molting, growth, and calcium and phosphate composition of tissue and molt during the grow-out of the giant freshwater prawn Macrobrachium rosenbergii (average weight 10.56 t 0.20 g), obtained from a grow-out pond, were studied. Intramuscular doses of vitamin D3 (100, 500 and 2000 IU/kg body weight) were given on the 1St, 3rd, 5th, 7th, 9th, 11th, 13th, 15th, 20th, 25 th and 30th days. All the experimental animals were fed with a basal diet containing fish meal, shrimp meal, wheat flour, groundnut de-oiled cake, soybean meal and wheat bran at 3% of the body weight. The numbers of molts were recorded as 20+0.50, 29+1.16, 51+1.87, and 30+1.60 in control, 100, 500 and 2000 IU/kg body weight physiological doses, respectively. Maximum growth was recorded in prawns given 500 IU/ kg dose. Survival was between 58.33 Â± 9.13 and 77.77 Â± 8.61%. The ash content and calcium level increased significantly (p<0.05) and recorded the highest values in 500 IU/kg physiological dose. However, the inorganic phosphate (P i) content recorded the highest values in tissue in 2000 IU/kg dose (p<0.05, F = 50.60613). There is no significant difference in calcium contents (p>0.05) in both tissue and molt at 500 and 2000 IU/kg doses. It was found that a higher physiological dose (2000 IU/kg) of vitamin D3 increased the rate of mortality. Results have shown that vitamin D3 has a positive impact on the growth and survival of M. rosenbergii and it interferes with the metabolism of Ca and P, in tissue, and alters molting frequency. Results on physiological dose suggest an alternative and effective dietory supplementation method of vitamin D3 in the grow-out phase of M. rosenbergii. Keywords: Vitamin D3 , growth, molting, calcium and phosphate, Macrobrachium rosenbergii